Novel Applications of Intelligent Systems - Hadjiski, Mincho; Kasabov, Nikola; Filev, Dimitar; Jotsov, Vladimir (Studies in Computational Intelligence, 2016)
In this carefully edited book some selected results of theoretical and applied research in the field of broadly perceived intelligent systems are presented. The problems vary from industrial to web and problem independent applications. All this is united under the slogan: "Intelligent systems conquer the world". The book brings together innovation projects with analytical research, invention, retrieval and processing of knowledge and logical applications in technology. This book is aiming to a wide circle of readers and particularly to the young generation of IT/ICT experts who will build the next generations of intelligent systems.